Child-peers talk: a preliminary study - Sankaran, Suguna; Badzis, Mastura (Zes Rokman Resources, 2017)
Talk between child and peers are apparent in every preschool. Talk enhances child’s communication and social skills besides developing one’s self confidence. In fact developing communication skills is one of the objectives highlighted in the preschool curriculum in Malaysia. This preliminary study was carried out to investigate the types of talk between child and peers during learning activities, in particular, individual task and free play sessions. The data arises from qualitative study investigating preschoolers aged 6 years old from two preschools in Klang district, Selangor, Malaysia. Twenty preschoolers aged six years old were drawn from purposive sampling, based on the preschool teachers’ suggestion of children who talk the most in the preschool classroom. This study is significant since there are limited studies in child-peers talk especially in preschools in Malaysia. Non-participant classroom observation was conducted and field-notes were taken during the observation. The findings of this preliminary study revealed two major types of child-peers talk, namely: on-task talk and off-task talk. Each type of talk was categorized further based on the thematic analysis of the data collected. Implication of this preliminary study showed that more opportunities should be given for children to engage in quality children talk.